Optimasi Sistem Pengendalian Frekuensi Dengan Metode Kontrol Optimal Linier Quadratic Regulator Pada PLTU - Hanifa, Muhammad Riski; Hasyim Rosma, Iswadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A good and efficient generating system is essential to meet the growing demand of electricity. Stability is required in the generation process to operate optimally. One of important stability parameters is frequency stability. This stability can be achieved by controlling the frequency of power plant (i.e. steam power plant). Turbine-generator is one of the important parts in generating system where it converts mechanical energy into electrical energy. On a turbine-generator, frequency becomes the main reference parameter that identifies the normal or abnormal condition of power plant. The main problem in the power plant is sudden load changes that result in abnormal system frequency (to drop or to rise). This abnormal frequency may cause damage on part of power plant, therefore it is necessary to adjust the flow rate of steam into the turbine to obtain the nominal speed of turbine by putting a proper gain controller. The gain was estimated by using LQR method. It has been found from the results that power plant with proper gain controller is better to bring the frequency back to normal compare to without controller.Keywords : Frequency, steam power plant, Optimal Control, Matlab/Simulink, LQR